2018
DOI: 10.3855/jidc.9720
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for bloodstream infections due to extended-spectrum β-lactamase producing Enterobacteriaceae in cancer patients

Abstract: Introduction: Bloodstream infection (BSI) caused by Enterobacteriaceae is associated with mortality in cancer patients receiving chemotherapy. The aim of this study is to identify the risk factors and outcomes related to BSIs caused by extended-spectrum beta-lactamase (ESBL)-producing Enterobacteriaceae in cancer patients. Methodology: Hematology/oncology patients, who were diagnosed with BSIs caused by Enterobacteriaceae by positive blood cultures were evaluated retrospectively. Patients were divided in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 35 publications
0
14
0
Order By: Relevance
“…reported that FN/ neutropenia was not the risk factor for mortality in BSIs caused by ESBL-PE among patients with malignancy. (14,16,21,24) Hence, the accuracy of the conclusion needs to be further confirmed. The combined RR of sensitivity analysis further confirmed the stability of the results.…”
Section: Discussionmentioning
confidence: 98%
See 3 more Smart Citations
“…reported that FN/ neutropenia was not the risk factor for mortality in BSIs caused by ESBL-PE among patients with malignancy. (14,16,21,24) Hence, the accuracy of the conclusion needs to be further confirmed. The combined RR of sensitivity analysis further confirmed the stability of the results.…”
Section: Discussionmentioning
confidence: 98%
“…(38,39) Interestingly, FN was not associated with higher mortality in oncological patients with BSIs caused by ESBL-PE, which could be attributed to there are only three studies included patients with FN, while some studies enrolled a subset of FN patients, but the data were not accessible to analysis. (13,14,16,21,24,25,30,34,40) Among these studies, Kang CI et al…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…At the same time, indwelling urinary catheter, (23) pneumonia, (31) Pitt bacteremia score, (32) and severe sepsis/ septic shock (31) were the most common independent risk factors of mortality in studies that only enrolled patients with BSIs caused by ESBL-PE. In studies that both included ESBL-PE and non-ESBL-PE infections, severe sepsis/ septic shock, (14,16,18,19,22,24,28,33) ICU admission, (14,19,27,33,34) neutropenia, (13,14,24,35) and pneumonia (14,16,21,28) were the most commonly investigated independent risk factors, respectively. Interestingly, there were only three studies (13,14,16) identi ed that ESBL production was associated with unfavorable outcomes in these patients.…”
Section: Predictors Of Mortality In Bsis Caused By Esbl-pe Among Patimentioning
confidence: 99%